ACUTE PAIN MANAGEMENT IN CATS: ASSURANCE OF FELINE WELFARE FULFILLMENT WITHIN CLINICAL SETTING - Gunawan, Michael; Utami, Nindya Dwi; Noviana, Deni (Buletin Veteriner Udayana; Vol. 15 No. 5 Oktober 2023, 2023)
Assessing, acknowledging, and managing pain in feline patients are often challenging. Failure to recognize and protect the cats from the harmful effects of nociception, therefore, often ensues. Feline patients that are afflicted with illness and tissue trauma that may arise from trauma or surgery have acute pain that needs to be addressed. Acute pain can present with varying degrees of intensity, a parameter of sensory-discriminatory aspect, and unpleasantness, a perceived feeling that is integral to affective aspect. Notwithstanding its usefulness to protect the tissue from further damage, acute pain is detrimental to the feline’s welfare, comprising physical and mental wellness if not managed properly. Uncontrolled pain has also been associated with increased morbidity, prolonged hospitalization period due to delayed recovery, increased health-care cost, and decreased quality of life. This review article is made with the aim to elucidate how acute pain in cats is recognized, prevented, and treated, both pharmacologically and non-pharmacologically.